Antimicrobial Activity of Black Cumin Seeds (Nigella sativa L.) - Erdogrul, zlem; iftτi, Edip; Bozdogan, Hakan; Toroglu, Sevil (Asian Journal of Chemistry, 2010)
This study was designed to examine the in vitro antimicrobial activity of Nigella sativa seed by the paper disc agar diffusion method. For this purpose, extracts of Nigella sativa seeds were prepared in ethyl acetate, methanol, acetone, hexane, diethyl ether, chloroform, ethanol tested on bacterial strains of Staphylococcus aureus ATTC 6538, Listeria monocytogenes SCOTT A, Bacillus megaterium NRS, Micrococcus luteus LA 2971, Bacillus subtilis ATTC 6633, Yersinia enterocolitica O:3 P 41797, Bacillus brevis EMC 33, Escherichia coli ATTC 8739, Bacillus megaterium DSM 32, Pseudomonas aeroginosa ATTC 9027, Klebsiella pneumoniae ATCC 13883, Enterococcus faecalis ATCC 15753, Salmonella typhimurium ATCC 13311, Serratia spp. (isolated in KSU) and Candida albicans ATTC 10194 as in vitro. The results were compared with ampicillin (10 mcg) and nystatin (30 mcg) standards. It was found that inhibitory activity of Nigella sativa seeds showed different levels of antimicrobial activity to all test strains.